Cycloferon in the Treatment of Immunocompromised Patients with Allergic Rhinitis - N. S. Tataurshchikova (Антибиотики и Химиотерапия, 2020)
The last few decades are characterized by the appearance of phenotypes of allergic rhinitis, the inflammatory cascade of which is realized in a complex process of interaction of infectious and allergic components. The infectious component in people with allergopathology is a herpes-viral infection, which often changes the clinical picture in such patients, the volume of pharmacotherapy, and the prognosis of the disease. The presence of chronic herpes-viral infection in immunocompromised patients presents this problem with particular urgency, since any viral infection is dangerous for the state of human health with allergies. Cycloferon is an effective and promising low-molecular inducer of interferon. The mechanism of action of cycloferon is an important link in the selection of immunomodulatory therapy for the treatment of herpesvirus infection. The article presents a scheme of using cycloferon in immunocompromised patients with allergic rhinitis. The combined use of local immunotherapy and allergen-specific sublingual immunotherapy (SLIT) in these patients is a highly effective method.